Encouraging Help Across Projects - Crama, Pascale; Sting, Fabian J.; Wu, Yaozhong (Management Science, 2019)
Companies struggle with timely project execution despite employing sophisticated management methods. Although help across projects is critical for time performance, it has not been explicitly incorporated into project management (PM) systems. We model a PM system, based on an innovative real-life practice, that both incorporates and shapes project managers’ helping behavior. A help process is at the core of this system, in which project managers may ask for and provide help while top management facilitates such exchanges. We find that companies should take a nuanced approach when designing help exchange and time-based incentives in tandem. A company that faces high project rewards after delays and highly effective help can benefit from inducing help because doing so enables the pursuit of projects it might abandon if delayed or even at the outset. The formal help process delivers value by creating and exploiting interdependencies between projects. These interdependencies allow project prioritization by inducing different effort levels in otherwise identical projects. A help process also allows the company to “tune” the timing of efforts by front-loading or back-loading project work. The benefits of a help system accrue through cost efficiencies, increased probability of success under help, and intertemporal incentive effects that encourage early efforts. However, because the help process creates the opportunity for free riding, a help system is not always recommended and a no-help system may perform better, especially when there are low project rewards after delay and low opportunity costs for project work. This paper was accepted by Serguei Netessine, operations management.